Reward-Based Decision-Making in Depression or At-Risk Population - Lin, Yiyan (Transactions on Materials, Biotechnology and Life Sciences, 2024)
This paper discussed the recent studies on the behavioral and neural patterns of individuals with depression and those with familial risk in reward-based decision-making. Current theories for depression and reward-based decision-making were presented so that they can pave the way for investigation of the interaction between the two under scrutiny. The paper argues that depression influences individuals’ aspects of reward-based decision-making, including thinking strategies, flexibility, reward perceptions, and motivation. At-risk populations inherited the same patterns. According to the empirical studies from recent years, results mainly support the argument. Both clinical and at-risk groups have conservative thinking strategies, inflexibility in demanding situations, and lower perceived reward salience. Furthermore, at-risk populations can obtain the same reward amount even though their neural signals indicate a diminishing reward salience. Future studies, such as longitudinal studies to scrutinize the effect of depression on clinical and at-risk populations, should seek insight into the long-term impact. Moreover, in the future, more studies should investigate the critical period for at-risk populations adopting inflexible thinking patterns so that clinicians can prevent depression in time.